On Harmonic Functions Defined by Differential Operator with Respect to k-Symmetric Points - Afaf A. Ali Abubaker; Maslina Darus (International Journal of Mathematics and Mathematical Sciences)
We introduce new classes MHkσ,s(λ,δ,α) and M¯Hkσ,s(λ,δ,α) of harmonic univalent functions with respect to k-symmetric points defined by differential operator. We determine a sufficient coefficient condition, representation theorem, and distortion theorem.